DESENVOLVIMENTO DE METODOLOGIA PARA DETECÇÃO DE FORMALDEÍDO EM AMOSTRAS DE LEITE POR CG-EM. - Vaz, Everton Barbosa (2021)
Milk is one of the most consumed foods in the world due to its high nutritional value. Because it has a pH close to neutrality, milk is a product conducive to the appearance of undesirable microorganisms. The milk industry(the dairy industry) has the obligation to supply a good quality product and the heat treatments have the function of eliminating the contamination present there. Industry must also supply a product that is free from any adulteration. The use of preservatives is the most common adulteration as/since formaldehyde for example, is used to eliminate microorganisms. Formaldehyde is a very toxic and carcinogenic compound and causes irreparable damage to the health of those who consume it. In the present study, a gas chromatography method for the determination of formaldehyde in milk samples was developed and validated. The methodology used was developed and applied to milk samples from twelve different brands with two lots of each make. The developed methodology allowed a quantitative analysis of formaldehyde in milk samples. The obtained results in this study lie within what was suggested by the European Food Safety Authority (EFSA), which is 0.1ppm - 0.8 ppm. Gas chromatography coupled to the mass spectrometer allowed for better analysis of the samples, providing better selectivity, precision and greater reliability of the results.